An Exploration of Teachers' Integration of Visual Literacy in the Egyptian Secondary English Language Classrooms - Asmaa Abdel-Moneim Mostafa (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2011)
Recognizing the need for students to be literate in  the more traditional areas of reading and writing, professional organizations such as the NCTE, IRA, and NCATE as well as NAQAAE, The National Authority for Quality Assurance and Accreditation of Education in Egypt, have put in place English language standards that address other literacies, including visual literacy. Yet, it has been unclear how secondary English language teachers feel about and understand what is expected of them in teaching non-print literacy, and if they indeed are teaching concepts related to comprehension and production of information in non-text format. This study attempts to discover teachers' attitudes toward, understanding of, and use of visual literacy concepts through a survey of the secondary English language teachers in Egypt. Based on the information from the responses to the survey, secondary English language teachers have received no formal training in teaching visual literacy and that their informal training consists mainly of discussions with colleagues and independent study; among others.